Social Capital and Gender Equity in Sports - Irene Kamberidou; Patsantaras, Nikolaos (2006)
When citing: Kamberidou, Irene & Patsantaras, Nikolaos (2006). "Social Capital and Gender Equity in Sports”. Presentation at the international conference Social Capital and Sport Governance in Europe: Trust and the Use of Social Ties, 4-5/12/2006, organized by the Universitat Commerciale Luigi Bocconi and IPAS- Institute of Public Administration and Health Care Management ‘Carlo Masini’, in collaboration with the European Commission, Milano Italy. © Irene Kamberidou presenting paper at Bocconi University, Milano 2006, at conference entitled  Social Capital and Gender Equity in Sports.